PENERAPAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA KELOMPOK TANI MANGGA GEDONG GINCU DALAM MENGHADAPI PASAR BEBAS - CHARINA, ANNE; ANDRIANI, RANI; SUPYANDI, DIKA; SUKAYAT, YAYAT (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
Mango Gedong Gincu (Mangifere var.Gedong indica) is one type of mango that is cultivated in West Java, particularly in Cirebon. Today the demand for mango Gedong Gincu from overseas customers is quite high. To achieve high competitiveness, especially in the face of free trade the use of Information and Communication Technology (ICT) by Farmers Group will be vital.The specific objective of this research to see ICT used by the groups, and to analyze the obstacles encountered in the use of ICTs in the era of free trade. The study was conducted in Kab.Cirebon. With Qualitative research design and use System thinking with causal loop diagram analysis tools.The results showed that the use of ICT farmer groups are radio, television, computer, mobile phone, tabloid / newsletter, leaflet, fax and internet. Constraints application of ICT in Suka Mulya Farmer Group is divided on the environmental constraints, constraints skills, and particularly cultural constraints. Variable levers major obstacles to the implementation of ICT is lack of motivation of farmers to try ICT. Persuasive approach from the government, the agent and other components involved is expected to change the paradigm of farmers more aware of the benefits of ICT.